Value of 18F-FDG PET/MRI in the Preoperative Assessment of Resectable Esophageal Squamous Cell Carcinoma: A Comparison With 18F-FDG PET/CT, MRI, and Contrast-Enhanced CT - Wang, Fei; Guo, Rui; Zhang, Yan; Yu, Boqi; Meng, Xiangxi; Kong, Hanjing; Yang, Yang; Yang, Zhi; Li, Nan (Frontiers in Oncology, 2022)
Objectives: To investigate the value of 18F-FDG PET/MRI in the preoperative assessment of esophageal squamous cell carcinoma (ESCC) and compare it with 18F-FDG PET/CT, MRI, and CECT. Methods: Thirty-five patients with resectable ESCC were prospectively enrolled and underwent PET/MRI, PET/CT, and CECT before surgery. The primary tumor and regional lymph nodes were assessed by PET/MRI, PET/CT, MRI, and CECT, respectively, and the diagnostic efficiencies were determined with postoperative pathology as a reference standard. The predictive role of imaging and clinical parameters on pathological staging was analyzed. Results: For primary tumor staging, the accuracy of PET/MRI, MRI, and CECT was 85.7%, 77.1%, and 51.4%, respectively. For lymph node assessment, the accuracy of PET/MRI, PET/CT, MRI, and CECT was 96.2%, 92.0%, 86.8%, and 86.3%, respectively, and the AUCs were 0.883, 0.745, 0.697, and 0.580, respectively. PET/MRI diagnosed 13, 7, and 6 more stations of lymph node metastases than CECT, MRI, and PET/CT, respectively. There was a significant difference in SUVmax, TLG, and tumor wall thickness between T1 - T2 and T3 tumors (p = 0.004, 0.024, and ˂ 0.001, respectively). Multivariate analysis showed that thicker tumor wall thickness was a predictor of a higher T stage (p = 0.040, OR = 1.6). Conclusions: 18F-FDG PET/MRI has advantages over 18F-FDG PET/CT, MRI, and CECT in the preoperative assessment of primary tumors and regional lymph nodes of ESCC. 18F-FDG PET/MRI may be a potential supplement or alternative imaging method for preoperative staging of ESCC.